INVESTIGATING LANGUAGE STYLE IN H3 PODCAST YOUTUBE CHANNEL - Meysi Natasya Sitepu; Arsen Nahum Pasaribu; Donna Ria Pasaribu (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aims to identify the types of language styles and determine the dominant style used by audiences in the YouTube comment section of the H3 Podcast channel. This research employs a descriptive qualitative approach based on Martin Joos’s theory of language style, which classifies language into five categories: frozen, formal, consultative, casual, and intimate. The data consist of English comments collected from three H3 Podcast videos with high audience engagement. The data were collected through documentation by selecting relevant comments and analyzed based on the linguistic characteristics of each language style. The findings reveal that four types of language styles are used, namely casual, intimate, consultative, and formal, with casual style being the most dominant. This dominance indicates that digital communication in YouTube comment sections tends to be informal, spontaneous, and expressive. The findings also confirm that Martin Joos’s theory remains relevant in analyzing language use in contemporary digital communication contexts.